2011
DOI: 10.1108/13665621111154395
|View full text |Cite
|
Sign up to set email alerts
|

Organizational commitment through organizational socialization tactics

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 52 publications
1
29
1
9
Order By: Relevance
“…Previous studies in the West have reported that supervisory support for training and OC are significantly related (Bartlett, 2001;Bulut & Culha, 2010) but some other studies found insignificant relation (Filstad, 2011) or significant but negative relation (Smeenk, Eisinga, Teelken, & Doorewaard, 2006). The reasons of such mixed results may partly be because of market imperfection in which a company is not always successful to employ a person whose skill is compatible to what the company needs.…”
Section: Training Provisioncontrasting
confidence: 38%
“…Previous studies in the West have reported that supervisory support for training and OC are significantly related (Bartlett, 2001;Bulut & Culha, 2010) but some other studies found insignificant relation (Filstad, 2011) or significant but negative relation (Smeenk, Eisinga, Teelken, & Doorewaard, 2006). The reasons of such mixed results may partly be because of market imperfection in which a company is not always successful to employ a person whose skill is compatible to what the company needs.…”
Section: Training Provisioncontrasting
confidence: 38%
“…Kleine et al (2005) noted that realism of pre entry knowledge and agent helpfulness, the two indicators of early socialization experiences, were associated with greater role clarity, job satisfaction, and organizational commitment. On the other hand, Filstad (2011) reported that there was no significant relationship between organizational socialization tactics on the context and content dimensions and affective organizational commitment. That means that facilitating formal training and timetables for career development does not necessarily lead to organizational commitment.…”
Section: Research Hypothesis Developmentmentioning
confidence: 97%
“…The evidences of different authors show, on the one hand, as the relations of mutual support and the support received from colleagues during the socialization, facilitates the creation of commitment to the organization (Calderon-Mafud et al, 2015;Filstad, 2004Filstad, , 2011Meyer et al, 1998;Mitus, 2006;Tierney, Bauer & Potter, 2002). On the other hand, training, emotional support and the functional understanding that a worker gets his companions acts to enable it to deal with the organizational changes that forced him to clarify their role constantly (Feldman, 1981).…”
Section: Organizational Socializationmentioning
confidence: 99%
“…Such characteristics are presented in the authentic leadership , Avolio, Gardner, Walumbwa, Luthans, & May, 2004Danielson, 2004;Gardner, Avolio, Luthans, May, & Walumbwa, 2005;Taormina, 2009). Moreover, it has been established that the Organizational Socialization is linked with the commitment and job satisfaction, as a result of workers perceive greater certainty to learn the rules of the job, get the support of their coworkers and to understand how it is the functioning of the organization (Autry & Daugherty, 2003;Chao, O'Leary-Kelly, Wolf, Klein, & Gardner, 1994;Filstad, 2004Filstad, , 2011Meyer, Allen, & Topolnystky, 1998;Mitus, 2006;Schmidt, 2010;Taormina, 1997;Tierney, Bauer, & Potter, 2002). However, there is little empirical evidence of the role played by the organizational socialization and leadership in the psychological states underlying productivity, like motivation and proactivity.…”
Section: Introductionmentioning
confidence: 99%